Effect of consolidation on the resilient response of soft soils in Mexico City - Alexandra Ossa; César Lerma; Mario Flores; Alberto Gaxiola (Case Studies in Construction Materials, 2022)
A methodology used to determine the resilient modulus of the foundation soil that comprises the area of lacustrine soils in Mexico City is presented, and the effect of a ground improvement procedure conducted using preload and prefabricated vertical drains is described. To achieve the objectives of the study, it was necessary to develop new criteria to determine the resilient modulus of such soft soil, which led to results with no precedent in the literature.